2008
DOI: 10.1128/jvi.01180-08
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of prM Cleavage, Extracellular Particle Distribution, and Virus Infectivity by Conserved Residues at Nonfurin Consensus Positions of the Dengue Virus pr-M Junction

Abstract: In the generation of flavivirus particles, an internal cleavage of the envelope glycoprotein prM by furin is required for the acquisition of infectivity. Unlike cleavage of the prM of other flaviviruses, cleavage of dengue virus prM is incomplete in many cell lines; the partial cleavage reflects the influence of residues at furin nonconsensus positions of the pr-M junction, as flaviviruses share basic residues at positions P1, P2, and P4, recognized by furin. In this study, viruses harboring the alanine-scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(147 citation statements)
references
References 54 publications
4
142
0
1
Order By: Relevance
“…Previous studies of flaviviral prM protein demonstrated the importance of the Arg-Xaa-Arg/Lys-Arg motif (at positions P4 to P1) for the cleavage of prM protein (11); moreover, charged residues adjacent to the consensus motif such as those at positions P3, P5, and P6 have been shown to affect the efficiency of prM cleavage (61). Based on the crystal structure of furin, the active site cleft consisting of 18 clustered negatively charged residues and S1, S2,and S4 subsite pockets may explain the stringent requirement of arginine at P1 and P4 and lysine at P2 (62).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of flaviviral prM protein demonstrated the importance of the Arg-Xaa-Arg/Lys-Arg motif (at positions P4 to P1) for the cleavage of prM protein (11); moreover, charged residues adjacent to the consensus motif such as those at positions P3, P5, and P6 have been shown to affect the efficiency of prM cleavage (61). Based on the crystal structure of furin, the active site cleft consisting of 18 clustered negatively charged residues and S1, S2,and S4 subsite pockets may explain the stringent requirement of arginine at P1 and P4 and lysine at P2 (62).…”
Section: Discussionmentioning
confidence: 99%
“…The prM S90R mutation is located at the P3 position of the cleavage site that potentially could improve the prM cleavage. A previous study of DENV-2 showed that a decrease in prM cleavage was associated with higher proportions of subviral particles and prM-containing virions in culture medium (11,13). On the other hand, enhanced prM cleavability adversely affects DENV-2 export and release (13).…”
Section: Superinfection Of Wnv Neorep Bhk-21 Cells Using Flavivirusesmentioning
confidence: 99%
“…The release of virions from the cell surface results in the loss of pr and resultant formation of a mature, infectious virion (Junjhon et al, 2008(Junjhon et al, , 2010Yu et al, 2008Yu et al, , 2009. prM is required for efficient trafficking of E to the cell surface and accelerated cleavage of prM is detrimental to virion production (Junjhon et al, 2008(Junjhon et al, , 2010Keelapang et al, 2004).…”
Section: Flavivirus M Proteinmentioning
confidence: 99%
“…The 75 aa small M (membrane) protein is cleaved from the viral E protein by signal peptidase as a prM precursor, which is then processed in the Golgi and acidifying secretory compartments by furinlike proteases into M and the pr peptide (Junjhon et al, 2008;Keelapang et al, 2004;Kuhn et al, 2002;Wong et al, 2012;Yu et al, 2008). The release of virions from the cell surface results in the loss of pr and resultant formation of a mature, infectious virion (Junjhon et al, 2008(Junjhon et al, , 2010Yu et al, 2008Yu et al, , 2009.…”
Section: Flavivirus M Proteinmentioning
confidence: 99%